Regulation of the Escherichia coli cad operon: location of a site required for acid induction. - Meng, S Y (1992)
The cad operon encodes lysine decarboxylase and a protein homologous to amino acid antiporters. These two genes are induced under conditions of low pH, anaerobiosis, and excess lysine. The upstream regulatory region of the cad operon has been cloned into lacZ expression vectors for analysis of the sequences involved in these responses. Deletion analysis of the upstream region and cloning of various fragments to make cadA::lacZ or cadB::lacZ protein fusions or operon fusions showed that cadA was translated more efficiently than cadB and localized the pH-responsive site to a region near an upstream EcoRV site. Construction of defined end points by polymerase chain reaction further localized the left end of the regulatory site. The presence of short fragments bearing the regulatory region on high-copy-number plasmids greatly reduced expression from the chromosomal cad operon, suggesting that titration of an essential activator protein was occurring. With nonoptimal polymerase chain reaction conditions, a set of single point mutants were made in the upstream regulatory region. Certain of these altered regulatory regions were unable to compete for the regulatory factor in vivo. The locations of these essential bases indicate that a sequence near the EcoRV site is very important for the activator-DNA interaction. In vivo methylation experiments were conducted with cells grown at pH 5.5 or at pH 8, and a difference in protection was observed at specific G residues in and around the region defined as important in pH regulation by the mutation studies. This work defines essential sequences for acid induction of this system involved in neutralization of extracellular acid.